The Effect of Fecal Microbiota Transplantation on a Child with Tourette Syndrome - Huijun Zhao; Yichao Shi; Xi Luo; Lihua Peng; Liping Zou; Yunsheng Yang (Case Reports in Medicine)
Tourette syndrome is a neuropsychiatric disorder with onset in childhood. New therapies are needed to effectively manage and treat this condition. Gut microbiota can affect central physiology and function via the microbiota-gut-brain axis. Here, we report a case in which fecal microbiota transplantation (FMT) is used to treat a child with Tourette syndrome, whose symptoms ameliorated dramatically in the following eight weeks.